2013
DOI: 10.1097/sla.0b013e3182822c8c
|View full text |Cite
|
Sign up to set email alerts
|

The Choice of Primary Repair or Mesh Repair for Paraesophageal Hernia

Abstract: Depending on what the decision-maker accepts as the recurrence and reoperation rates for these types of repair, either mesh or primary repair may be the treatment of choice. However, the differences between the two are small, and, perhaps, clinically inconsequential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Controversy exists around the reinforcement of the diaphragmatic crura, as well as the type of the graft used, and the value of the graft in preventing recurrence, around short-and long-term complications, and the consequences of those complications compared with primary repair [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Controversy exists around the reinforcement of the diaphragmatic crura, as well as the type of the graft used, and the value of the graft in preventing recurrence, around short-and long-term complications, and the consequences of those complications compared with primary repair [14].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the quality of life improved significantly after all types of hernia repair [21]. According to the most recent reviews, either mesh repair or primary repair may be the treatment of choice, based on the decision made by individual surgeons, and depending on their own recurrence and reoperation rates [14]. With regard to the choice of mesh, it should also be at the discretion of the surgeon based on his/her experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gibson et al [27] have recently suggested that mesh is not required for a successful outcome and Obeid et al [28] have published a decision-based analysis suggesting the differences between the use of mesh and primary repair are small. However, the majority of studies reviewed, and most existing data published to date, involved patients being randomized to mesh or primary repair with no differentiation in the characteristics of the hernial defect.…”
Section: Discussionmentioning
confidence: 98%
“…These complications include gastric and esophageal erosions, strictures of the gastroesophageal junction, and dysphagia. 17 The overwhelming majority of these complications require additional surgeries. In extreme cases, an esophagectomy may be required.…”
Section: Discussionmentioning
confidence: 99%